Systemic manifestations and symptom burden of facioscapulohumeral muscular dystrophy in a referral cohort. Issue 4 (25th January 2022) - Kelly, Cecilia R.; Saw, Jacqui‐Lyn; Thapa, Prabin; Mandrekar, Jay; Naddaf, Elie
Abstract: Introduction/Aims: The full spectrum of the clinical phenotype of facioscapulohumeral muscular dystrophy (FSHD), beyond skeletal muscle weakness, remains poorly characterized. In this study, we describe systemic manifestations and symptom burden in a large series of FSHD patients. Methods: We performed a retrospective chart review of FSHD patients seen at our institution between 2000 and 2017. We reviewed patients' responses to a comprehensive review of symptoms and the results of diagnostic testing for sensorineural hearing loss, cardiac disease, dysphagia, ocular abnormalities, and respiratory insufficiency. We assessed the association between disease manifestations and age of onset, genetic profile, and disease duration. Results: We identified 87 patients with FSHD. The most common reported symptoms included pain (71%), difficulty sleeping (41%), headaches (27%), and altered mood (24%). When tested, 7 of 16 (44%) patients had sensorineural hearing loss, 20 of 60 (33%) had cardiac arrhythmias or conduction defects, 17 of 45 (38%) had echocardiogram abnormalities, 12 of 25 (48%) had reduced forced vital capacity, and 4 of 10 (40%) had oropharyngeal dysphagia. However, patients with these abnormalities represented 8%, 23%, 20%, 14%, and 5% of total number of patients, respectively, as uniform screening was lacking. Ocular pathology attributable to FSHD was not detected. Discussion: FSHD demonstrates a broad clinical phenotype. Increased vigilance among neurologists to screen for systemic manifestations of the disease is warranted. More uniform screening and future population‐based studies are needed to compare findings in FSHD patients with the general population.